Velid Ebuzziya’nın mektuplarına göre Lozan - Temiz, Ahmet (My University, 2005)
Lozan Konferansı, Osmanlı Devleti’nin dağılmasından sonra kurulmuş olan Türkiye Cumhuriyeti’nin uluslararası platformda tanınmasına vesile olmuştur. Yani bu konferans ve neticesindeki antlaşmayla yeni Türkiye Devleti’nin varlığının birçok dünya devletince kabul edildiği bir atlaşma özelliğine sahiptir. Çünkü bu antlaşmayla yeni Türkiye Cumhuriyeti Devleti’yle muhatapları olan diğer ülkeler arasındaki adlî, iktisadî, mâlî vb. birçok önemli alandaki ilişkileri düzenlenmiş, devletin bu ülkelerle başlayacak olan ilişkilerinin temelleri atılmıştır. Bizim yapmış olduğumuz bu çalışma da, bir devletin başlangıcı ve geleceği için bu derece öneme sahip bir antlaşmanın görüşmelerinin yapıldığı ve sonuca bağlanmış olduğu bu Konferans’a delegelerle beraber katılmış bir gazeteci olan Velid Ebuzziya’nın konferansın devam etiği esnada orada yazıp Türkiye’ye göndermiş olduğu mektuplardır. Tevhid-i Efkar Gazetesi’nin sahibi ve yazı işleri sorumlusu olan Velid Bey, 23 Nisan 1923’te başlayan ikinci Lozan Konferansı’na katılan gazetecilerden birisidir. Velid Bey yola çıkıldıktan sonra ve konferans devam ettiği sırada yazmış olduğu mektuplarını Tevhid-i Efkar Gazetesi’ne göndermiş ve bu mektuplar gazetede muhtelif günlerde “ Lozan Mektupları ” başlığıyla 95 adet olarak yayınlanmıştır. Yapmış olduğumuz bu çalışma, ülkemizin tarihinde çok önemli bir yeri olan Lozan Antlaşması’nın, bu antlaşmanın canlı şahitliğini yapmış olan bir gazetecinin kaleminden yorumlanmasıdır. Bu çalışmamızın araştırmacılara ve özellikle Lozan Konferansı üzerinde çalışmalar yapan tarihçilerimize faydalı olacağı kanaatindeyiz ve böyle olmasını temenni ediyoruz. Lozan Mektupları toplam 95 adet olup bunlardan 6 ve 67 mektuplara ulaşılamamıştır. ABSTRACTION After the First World War Truce of Montrose (Oct. 30, 1918) were signed first and then the Treaty of Sevres (Aug. 10, 1920) between the Allied powers and Ottoman Empire. Sevres was so harsh and hard to accept. Therefore the National Defense which began by the visit of Samsun by Mustafa Kemal went on spreading, and the enemy which invaded many parts of Anatolia was defeated. Allied Powers could be silent no more and told the governments of Ankara and Istanbul to start the negotiations of peace in the city of Lausanne of an impartial state (Oct. 27, 1922). Therefore Ahmed Vefik Pasha mentioned the necessity of acting together by a telegram to the Turkish National Assembly and wanted Ankara to send a delegate with theirs. The Allied powers were aiming at benefiting the conflict between the two by calling them apart. While this issue was being disputed the Rıza Nur, the Minister of Health, Hüseyin Avni Ulaş and his seventy-five friends wanted the ending of the Empire to be accepted by a proposal. And with a bill that was accepted in the 1st November 1922 it was announced that sultanate and caliphate was divided and sultanate was abolished. And by that way Turkish National Assembly went to the Conference as one responsible body. As a result of the proposals of the Allied powers it was admitted to gather in the city of Lausanne, Switzerland. The Peace Conference gathered in the 20th November of 1922 at 4 pm in the Casino Mont Benon in Lausanne. It was started by the speech of Habab, the chief of the Impartial Switzerland Confederation. After Lord Curzon İsmet Pasha had a speech stressing the importance of independence of us and said: “we just want freedom and independence as the other entire nations do”. After so many perverse disputes there was no way; and negotiations were cut in the 4th of February. Then it was gathered in the 23rd of 1923 and the Contract of Peace was signed. The Peace of Lausanne, after so much hard negotiations was signed in the ceremony hall of the University of Lausanne. All of the documents that were signed in Lausanne were the main Peace contract, 16 pieces of agreement, a protocol, manifesto and a last promissory note. It was not just an agreement between the two sides but was a rearrangement of the political, legal, economical and social relations. In the preface of the Contract the principal of respect for the freedom and sovereignty of the states was mentioned. This paragraph could be seen as signal of the Turkish side’s political struggle under the same conditions with the winners of The First World War. And also it was important in the sense of the acceptance of the Turkish freedom and sovereignty. The Main Peace Contract contains a preface and 143 items. The important regulations made in the Lausanne Peace Contract could be enumerated in the titles: matter of borders, the minorities, the capitulations, the compensation, the debts, the mending, and the straits and the exchange of population. This study we made is the letters of a journalist, named Velid Ebuzziya, who went to the Conference, which was so much important as being the place for the negotiations and decision of birth and future of a state, with the delegates. The letters, he wrote there and sent to Turkey. Velid Bey, who was the owner and responsible body for writing service, was one of the journalists that went to the second Lausanne Conference starting in the 23rd April 1923. He sent his letters after he set for the conference and when it was going on and these letters were serialized in the journal, Tevhid-i Efkar, as being 95 items in the title of “Lausanne Letters”. This study we made is a rereading of the Lausanne, which has a principal space in the history of our state, from the lines of a man that was a witness at that time. We assume this study could be of much use for the historians studying on Lausanne Conference, and also hope so. Lausanne Letters were 95 but we could not reach the letters numbered 6 and 67.
Keywords: Antlaşmalar_Lozan Barış Antlaşması; Mektuplar_Tarih; Türkiye_Tarih